VENTROMEDIAN FOREBRAIN DYSGENESIS FOLLOWS EARLY PRENATAL ETHANOL EXPOSURE IN MICE - Godin, Elizabeth A. (2010)
Ethanol exposure on gestational day (GD) 7 in the mouse has previously been shown to result in ventromedian forebrain deficits along with facial anomalies characteristic of fetal alcohol syndrome (FAS). To further explore ethanol's teratogenic effect on the ventromedian forebrain in this mouse model, scanning electron microscopic and histological analyses were conducted. For this, time mated C57Bl/6J mice were injected with 2.9 g/kg ethanol or saline twice, at a four hour interval, on their 7(th) day of pregnancy. On GD 12.5, 13 and 17, control and ethanol-exposed specimens were collected and processed for light and scanning electron microscopic analyses. Gross morphological changes present in the forebrains of ethanol-exposed embryos included cerebral hemispheres that were too close in proximity or rostrally united, enlarged foramina of Monro, enlarged or united lateral ventricles, and varying degrees of hippocampal and ventromedian forebrain deficiency. In GD 12.5 control and ethanol-exposed embryos, in situ hybridization employing probes for Nkx2.1 or Fzd8 to distinguish the preoptic area and medial ganglionic eminences (MGE) from the lateral ganglionic eminences, respectively, confirmed the selective loss of ventromedian tissues. Immunohistochemical labeling of oligodendrocyte progenitors with Olig2, a transcription factor necessary for their specification, and of GABA, an inhibitory neurotransmitter, showed ethanol-induced reductions in both. To investigate later consequences of ventromedian forebrain loss, MGE-derived somatostatin-expressing interneurons in the subpallial region of GD 17 fetal mice were examined, with results showing that the somatostatin-expressing interneurons that were present were dysmorphic in the ethanol-exposed fetuses. The potential functional consequences of this insult are discussed.